2022
DOI: 10.2340/actadv.v102.2738
|View full text |Cite
|
Sign up to set email alerts
|

No Association Between First Exposure to General Anaesthesia and Atopic Dermatitis in the Paediatric Population

Abstract: General anaesthesia could affect various immune responses, including Th1 and Th2 immunity, which might also affect cells that play an important role in the pathogenesis of atopic dermatitis. However, the relationship between general anaesthesia exposure and atopic dermatitis remains unknown. The aim of this study was to investigate the risk of developing atopic dermatitis after first exposure to general anaesthesia in the paediatric population (18 years or under). A retrospective cohort study, including those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Our previous study reported that children receiving GA exposure before one year of age reduced the risk of developing allergic diseases, including asthma, allergic rhinitis, and atopic dermatitis, by approximately 25–40% [ 34 ]. However, one study of children’s exposure to GA did not demonstrate either an increased or decreased risk of atopic dermatitis (2.3%) compared to the non-GA-exposed group (2.2%) when followed up for two years after cohort entry [ 51 ]. The authors stated that board-certified dermatologists only diagnosed the participants in that study with subsequent atopic dermatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study reported that children receiving GA exposure before one year of age reduced the risk of developing allergic diseases, including asthma, allergic rhinitis, and atopic dermatitis, by approximately 25–40% [ 34 ]. However, one study of children’s exposure to GA did not demonstrate either an increased or decreased risk of atopic dermatitis (2.3%) compared to the non-GA-exposed group (2.2%) when followed up for two years after cohort entry [ 51 ]. The authors stated that board-certified dermatologists only diagnosed the participants in that study with subsequent atopic dermatitis.…”
Section: Discussionmentioning
confidence: 99%